STUDIES ON THE ECONOMICS OF ALTERNATIVE WHEAT ESTABLISHMENT METHODS AND WEED MANAGEMENT PRACTICES - SEN, DHIMAN; SINGH, ROHITASHAV (Annals of Agricultural Research, 2014)
Better growing condition owing to good tills and proper weed suppression gave maximum production under conventional tillage in combination with two hand weedings at 30 and 50 DAS stage and ultimately, that attributed highest gross return (Rs. 34353 ha-1), although, more number of tillage operations and hand weedings also contributed maximum costinvolvement (Rs. 13628 ha-1) under this treatment combination. On the other hand, more production under conventional tillage and less cost requirement under isoproturon at 1.0 kg ha-1 treatment finally resulted into maximum net return (Rs 21089 ha-1) under conventional system along with isoproturon at 1.0 kg ha-1 treatment combination. Moderately higher yield and less cost of cultivation due to single operation for land preparation and sowing finally contributed maximum benefit cost ratio (2.09) under the treatment combination of still till drill along with isoproturon at 1.0 kg ha-1.